Correlation of plasma d-dimers with stages of liver cirrhosis and its complications. - Volkanovska, Anche; Dejanova, Violeta; Andreevski, Vladimir; Trajkovska, Meri; Labudovikj, Danica (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2023)
To investigate plasma D-dimer levels in correlation with Child-Pugh-Turcotte (CTP) and Model for End-Stage Liver Disease (MELD) scores in patients with liver cirrhosis (LC) of different severity, as well as the correlation with LC-associated clinical, biochemical parameters and complications. Material and methods: Fifty patients with LC were divided in three groups according to LC severity using the CTP Score (CTP-A, CTP-B, CTP-C). The levels of D-dimer were measured in sodium-citrate plasma on Siemens, BCS XP Blood Coagulometer. Kruskal-Wallis test was used to compare D-dimer levels between the groups. Mann-Whitney U test was used to evaluate the difference of D-dimer levels in groups with different MELD score, and to evaluate the difference in D-dimer levels in patients with presence or absence of ascites and the difference of D-dimer levels in patients with or without spontaneous bacterial peritonitis (SBP). Pearson’s coefficient of correlation was used to evaluate the correlation between D-dimer levels with MELD score and the correlation between D-dimer levels and the concentration of LC-associated biochemical, clinical parameters and complications. Results: D-dimer levels increased with severity of the disease as assessed with CTP and MELD scores, with a statistically significant difference between the groups (p=.0000 and p=.0001, respectively). Group CTP-C demonstrated the highest D-dimer levels, followed by groups B and A. Patients with SBP had significantly higher levels of D-dimers than patients without SBP (p=.0006). A significant positive correlation between D-dimers and CTP and MELD score was detected (r= 0.74 and r=0.44, respectively; p<.001). A correlation between D-dimer levels and several biochemical parameters characterizing progressive liver dysfunction was observed. From all investigated biochemical parameters, the highest significant correlation was detected between D-dimer levels and the concentration of serum albumin (r= -0.65, p<.001). Conclusions: Plasma D-dimer levels are tightly correlated with the degree of liver dysfunction and LC-associated complications. Therefore, D-dimer levels could be utilized as a prognostic stratification marker and adjunctive diagnostic marker in LC-associated complications.
Keywords: liver cirrhosis; D-dimer; hyperfibrinolysis; Model for End-Stage Liver Disease; Child-Pugh-Turcotte